(untitled) (International Journal of Built Environment and Sustainability, 2017)
The study appraises the preferred team role of construction team members in selected higher institution projects in Nigeria, with a view to improving delivery of such projects. The study used purposive sampling technique to select two higher institutions studied and census survey was used in selecting 35 completed construction projects executed by the institutions. A total of 191 questionnaires were distributed to obtain information from construction team members who participated in the selected construction projects. Mean Item Score was used in ranking the preferred team roles of construction team members. The results revealed that the construction team members’ preferred team roles by personal assessment are different from their preferred team roles by other observers’ assessment of individual construction team members. Construction team members have more than one preferred team roles and that the most preferred team role of Quantity surveyors, clients and contractors is resource investigator while the most preferred team role of Architects, Structural/Civil Engineers and Service Engineer is Planter, Implementer/company worker and specialist respectively. The study concluded that a deliberate attempt should be made in determining the preferred team roles of construction team members before co- opting them into a team so as to improve construction projects delivery.